A presença da dimensão sociopolítica no trabalho de formação do docente-formador - Nogueira, Makeliny Oliveira Gomes (2008)
The present study had as objective researches the presence of the sociopolitical dimension in the work of formation of the educational-former, bringing for the debate the reflection about the purpose of the education work. In this research, based on the socio-historical perspective and according to authors that follow this theoretical line, we started from the idea that every teacher's work has a sociopolitical dimension, because in any education work there is implicit or explicit a relationship among education and society, that is expressed in the purpose of the developed work. The subject raised in this paper work is to identify, through the voice of the educational-former, how clear for them is the presence of that dimension in their formation work in pedagogy degree courses, and which aspects he demonstrates to characterize that presence. To accomplish that study, fifteen questionnaires were applied to educationalist of public and private universities of the states of Paraná and São Paulo, and deeply interviews with four educational-formers of three universities of the Paraná state. The results pointed out that the teacher doesn't ignore the presence of the sociopolitical dimension in his work, but when characterizing that dimension, he makes it in a generic and ingenuous way